The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.2331/suisan.59.157
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Soybean Meal for Rainbow Trout and Carp.

Abstract: The nutritional quality of commercial defatted soybean meal (SBM) as a protein source was evaluated by determining apparent digestibility, PER, NPU, and BV. Two experiments were conducted using rainbow trout and carp with initial weights of 4.0 and 3.2g, respectively. They were fed diets containing SBM as the sole protein source at different protein levels from 0 to 75% for 20 days.The apparent protein digestibility was relatively high both in rainbow trout (92% on average) and in carp (91% on average). The PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 4 publications
2
18
0
1
Order By: Relevance
“…Khan et al (2012) reported that incorporation of plant protein by replacing fishmeal did not have a significant effect on the whole body composition of Indian major carps, Catla catla, Labeo rohita and Cirrhinus mrigala. Similarly, Pongmaneerat and Watanabe (1993) reported use of soybean meal as the sole protein source, the body protein content of carps was not greatly influenced.…”
Section: Soybean As Partial Substitute Of Fish Meal For Rohu Frymentioning
confidence: 88%
“…Khan et al (2012) reported that incorporation of plant protein by replacing fishmeal did not have a significant effect on the whole body composition of Indian major carps, Catla catla, Labeo rohita and Cirrhinus mrigala. Similarly, Pongmaneerat and Watanabe (1993) reported use of soybean meal as the sole protein source, the body protein content of carps was not greatly influenced.…”
Section: Soybean As Partial Substitute Of Fish Meal For Rohu Frymentioning
confidence: 88%
“…Além disso, está disponível nos mercados mundiais a um custo relativamente baixo comparando-se à farinha de peixe (FERNANDES, 1998). PONGMANEERAT & WATANABE (1993) trabalharam com alevinos de carpas (Cyprinus carpio) e trutas (O. mykiss) concluindo que o farelo de soja constitui-se em boa alternativa como fonte protéica para ambos, porém salientam que existe a necessidade de suplementação de lisina, arginina, cistina e triptofano. Já para o bagre norte-americano (Ictalurus punctatus), WILSON (1984) salienta que a proteína da soja não é deficiente em qualquer aminoácido essencial.…”
unclassified
“…In Japan, an alternative protein source for fish meal has been the focus of attention in recent years because of falling catches of sardine which are the main ingredients in the diet, and studies on substitutional protein sources have been started with the yellowtail. 1-7) Many papers have been written on substitutional protein sources with various kinds of fish such as rainbow trout, [8][9][10][11][12] carp, 13-16) tilapia, 17,18) and catfish. 19,20) However, in formation on flatfish is scarce.…”
mentioning
confidence: 99%